(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
The digital metamedia is the current space for social interaction par excellence. An ideal prosthetic memory for the creation of heterogeneous fictions, which result from post-production aesthetics of an e-image that establishes a new scopic regime. It will therefore be analyzed how this environment presents a fertile field for the replication of phenomena such as fakes, which can also proliferate as minimal units of cultural transmission (memes). This establishes a memecracy from which to activate subversive artistic practices.